The economic impacts and political repercussions of imposing tariffs on poultry imports in Saudi Arabia - Yosef Alamri; Atheer Al-Muhaini (Journal of the Saudi Society of Agricultural Sciences)
Abstract This study employs a modified Computable General Equilibrium (CGE) model to investigate the economic impacts of varying tariff rates on poultry imports in Saudi Arabia. The analysis integrates actual production, export, and import data alongside theoretical assumptions to assess the implications of increased tariffs from 20 to 35% on domestic poultry production and overall economic welfare. Contrary to the protective intent of tariffs, the findings indicate that higher tariffs lead to increased import prices but surprisingly result in a decline in domestic production. Specifically, production decreased by 17.5% under the highest tariff rate, accompanied by significant economic welfare losses amounting to $1.85 billion, primarily due to reduced consumer surplus and increased market inefficiencies. These results highlight the complexities and unintended consequences of tariff imposition in an import-dependent economy and suggest that alternative strategies such as subsidies, technological investments, and regional trade agreements may offer more sustainable benefits. The study underscores the need for a nuanced approach to trade policy, emphasizing the importance of comprehensive data analysis and dynamic economic modeling to inform policy decisions.